The effect of Methylphenidate on Energy Expenditure in Individuals with Obesity: A Randomized, Double-Blind, Placebo Controlled Pilot Trial - Hafizi, Kaamel (Université d'Ottawa / University of Ottawa, 2019)
Objectives: Most weight loss medications target reductions in energy intake while neglecting energy expenditure, a critical predictor of weight loss/regain. This pilot study examined the effect of short-acting methylphenidate (MPH) on resting energy expenditure (REE), thermic effect of food (TEF), physical activity energy expenditure (PAEE), and how changes in energy expenditure relate to changes in body composition in youth and adults living with obesity. Methods: This study was a randomized, double-blind, placebo-controlled two-parallel arm study. In total, 19 participants were screened, of which 14 participants were randomized into the study, but complete data was only collected for 12, and only analyzed for 10 participants. Those 10 participants aged 28.8 ± 6.9 yrs. (5 Male, 5 Female) were randomized to receive either MPH (0.5 mg/kg) (n = 5) or placebo (n =5) twice daily for 60 days. Participants’ REE and TEF (indirect calorimetry), were measured at baseline (no drug/placebo), and day 60 post-treatment (drug/placebo). Participants’ PAEE (Actical) was measured between screening and baseline for a 1-week period (no drug/placebo), and on day 53 for a 1-week period (drug/placebo). Participants’ anthropometrics were measured using DEXA at baseline, and day 60 post-treatment. Results: From baseline to day 60, MPH showed a relative difference to placebo in relative REE (Relative REE: F(1, 8) = 4.235, p = 0.074, d = 0.83, 2 = 0.346) of 10%, evidenced by a 6% increase in relative REE kcal/kg (18.53 ± 1.97 Kcal/day/kg at baseline, 19.71 ± 2.52 Kcal/day/kg at final) for the MPH group, and a 4% decrease (19.08 2.36 Kcal/day/kg at baseline, 18.26 ± 2.04 Kcal/day/kg at final) in placebo, translating to moderate-effect size (Cohen’s d=0.63) favouring MPH. From baseline to day 60, there were no significant differences between groups on changes in TEF (TEF AUC: F(1, 8) = 0.079, p = 0.785, d = 0.15, 2 = 0.010) or any PAEE variables such as sedentary behavior (SB: F (1, 8) = 0.455, p = 0.52, d = 0.02, 2 = 0.054), light physical activity (LPA: F (1, 8) = 0.504, p = 0.50, d = 0.16, 2 = 0.059), moderate physical activity (MPA: F (1, 8) = 0.281, p = 0.61, d = 0.19, 2 = 0.034), moderate-to-vigorous physical activity (MVPA: F (1, 8) = 0.120, p = 0.74, d = 0.15, 2 = 0.015), or vigorous physical activity (VPA: F (1, 8) = 3.495, p = 0.098, d = 0.91, 2 = 0.304) . Mean change in body weight (kg) resulted in a weight loss of roughly -2.66 ± 2.00 kg in the MPH group and -1.64 ± 1.41 kg in the placebo group, differences that were not statistically significant. Mean change in both groups for body fat% of -0.33 ± 2.08 %, mean change in fat mass of -1.05 ± 2.59 kg, and finally a mean change in fat-free mass of -0.06 ± 1.19 kg was reported. Changes in relative REE were inversely correlated with changes in body weight (r = -0.599, p = 0.067), body fat (r = -0.524, p = 0.12) and fat mass (r = -0.599, p = 0.096). These associations were stronger in the MPH group. Conclusions: Our data suggests that MPH administration may lead to a meaningful increase in relative REE, and these suggested changes were associated with reductions in adiposity among individuals with obesity. These preliminary findings suggest that MPH should be further examined using a larger sample size and study duration to determine its effectiveness in promoting weight loss and maintenance of weight loss in individuals with obesity, a population at high risk of morbidity and premature mortality.
Keywords: Energy Expenditure; Methylphenidate; Obesity; Physical Activity; Intervention; Resting Energy Expenditure; Thermic Effect of Food; Dopamine; Placebo; Ritalin